A non-glutaraldehyde cross-linked heart valve and its preparation method and use
By crosslinking the pig pericardium by using the non-glutaraldehyde crosslinking agent OX-Br and introducing betaine methacrylate sulfonate to form a multifunctional heart valve material SA@OX-PP, the glutaraldehyde crosslinking valve was solved. The problems of short lifespan and poor biocompatibility achieve excellent biocompatibility and anti-calcification properties, and are suitable for high-demand artificial biological valves.
Patent Information
- Application Number
- CN202310068769.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-06
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-02-06
AI Technical Summary
The existing artificial heart valves with glutaraldehyde crosslinking have short lifespans, are prone to calcification and thrombosis, and the residue of crosslinking agents leads to poor biocompatibility, limiting their clinical application.
The non-glutaraldehyde crosslinking agent OX-Br is used to cross-link with the pig pericardium, and the betaine methacrylate sulfonate is introduced through in situ polymerization to form a multifunctional heart valve material SA@OX-PP, which has anti-protein adhesion, Antibacterial adhesion, anticoagulation and pro-endothelial properties.
It significantly improves the biocompatibility, anti-calcification performance and service life of heart valves, reduces immune rejection, avoids the biocompatibility problems of glutaraldehyde crosslinking agents, and is suitable for a wider range of artificial biological valve applications.
Smart Images

Figure CN116173302B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biological heart valve materials, and in particular relates to a non-glutaraldehyde cross-linked heart valve and a preparation method and application thereof. Background Art
[0002] With the growth of population and the development of aging, more and more people are suffering from heart disease. Valvular heart disease, as a heart disease, threatens the lives of more than 100 million patients worldwide. However, due to the special physiological environment of heart valves, there is currently no specific drug for the treatment of valvular heart disease. Replacing heart valves with artificial heart valves is currently the best way to treat severe valvular heart disease. There are two types of artificial heart valves in clinical use: mechanical valves and biological heart valves (BHV). In recent years, with the development of minimally invasive interventional technology, transcatheter heart valve replacement (THVR), which has less trauma and faster recovery, has become the main solution for heart valve treatment. Compared with mechanical valves, BHV has superior hemodynamic properties, good anticoagulant properties and satisfactory compressibility, and has become the first choice for THVR. In recent years, the demand for BHV in clinical applications has been increasing.
[0003] Commercial artificial BHVs are usually made of porcine pericardium (PP) or bovine pericardium (BP) cross-linked with glutaraldehyde (Glut) to enhance the mechanical properties of the biomaterial and prevent degradation of the biomaterial after implantation. However, the fatal disadvantage of this type of BHV is its short lifespan, and the BHV after THVR can only be used for 10-15 years. Therefore, it is necessary to extend the service life of BHVs to serve a wider patient population. Studies have found that calcification is the primary problem that needs to be urgently solved for BHVs treated with glutaraldehyde. Calcification can harden the BHV, restrict its movement, and ultimately cause the BHV to fail to function normally and reduce its service life. At the same time, thrombosis is another reason why glutaraldehyde-treated BHVs have a short service life in clinical applications. In addition, the high toxicity of the residual aldehyde groups on the surface of the BHV treated with glutaraldehyde will also limit the adhesion and proliferation of endothelial cells, and the loss of the endothelial layer on the valve surface will further aggravate the formation of calcification and thrombosis.
[0004] In the past few decades, researchers have tried many ways to solve the problems of glutaraldehyde-treated artificial heart valves. Some non-glutaraldehyde compounds, such as epoxides, genipin, and carbodiimide, have been used to explore the possibility of cross-linking BHVs. However, most non-glutaraldehyde compounds cannot solve the basic problems of BHV mechanical properties and calcification, and non-glutaraldehyde cross-linked BHVs have not yet been further applied in clinical practice.
[0005] The literature (T.Yu et al; Nonglutaraldehyde treated porcine pericardium with good biocompatibility, reduced calcification and improved Anti-coagulation for bioprosthetic heart valve applications; Chemical Engineering Journal 414(2021)128900) reported a non-glutaraldehyde heart valve cross-linker: hydroxymethylbicyclic oxazolidine (OX-OH), and prepared an OX-OH cross-linked BHV (OX-OH-PP) using OX-OH and porcine pericardium as raw materials. Compared with glutaraldehyde cross-linked BHV, OX-OH-PP not only maintains similar mechanical properties, but also exhibits better anti-calcification properties and biocompatibility. However, in order to meet clinical needs, the biocompatibility, anti-protein adhesion, anti-bacterial adhesion and pro-endothelialization properties of OX-OH-PP still need to be further optimized to expand its application in artificial bioprosthetic valves with high comprehensive requirements such as heart valves, pulmonary valves, and venous valves. Summary of the invention
[0006] The purpose of the present invention is to provide a novel non-glutaraldehyde valve crosslinking agent and a non-glutaraldehyde crosslinked heart valve material prepared by using the non-glutaraldehyde valve crosslinking agent.
[0007] The present invention provides a valve cross-linking agent, the structure of which is shown below:
[0008]
[0009] The present invention also provides a biological valve material, which is a product prepared by using pericardium and the above valve cross-linking agent as raw materials.
[0010] Furthermore, the pericardium is decellularized pericardium, preferably decellularized porcine pericardium.
[0011] The present invention also provides a method for preparing the above-mentioned biological valve material, which comprises the following steps: immersing the pericardium in a valve crosslinking agent solution, reacting at 35-40°C for 3-7 days to obtain the biological valve material; the mass concentration of the valve crosslinking agent solution is 3%-7%.
[0012] Furthermore, the reaction temperature is 37° C., the reaction time is 5 days, and the mass concentration of the valve cross-linking agent solution is 5%.
[0013] The present invention also provides a multifunctional biological valve material, which is a product obtained by atom transfer free radical polymerization reaction between the above biological valve material and methacrylic acid sulfonate betaine.
[0014] The present invention also provides a method for preparing the above-mentioned multifunctional biological valve material, which comprises the following steps: immersing the above-mentioned biological valve material in a solution containing methyl methacrylate sulfonate betaine, removing oxygen, adding a ligand and a catalyst, performing an atom transfer radical polymerization reaction, and purifying to obtain the multifunctional biological valve material.
[0015] Furthermore, in the solution containing methacrylic acid sulfonate betaine, the concentration of methacrylic acid sulfonate betaine is 45-50 mg / mL; the ligand is 1,1,4,7,10,10-hexamethyltriethylenetetramine, the catalyst is CuCl2 and CuCl, and the molar ratio of methacrylic acid sulfonate betaine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, CuCl2 and CuCl is 1:(2-8):(0.2-0.8):(1-4); the temperature of the atom transfer radical polymerization reaction is 20-30°C and the time is 24-72 hours; the purification method is to soak in an ethylenediaminetetraacetic acid solution and then wash with water.
[0016] Furthermore, in the solution containing methacrylic acid sulfonate betaine, the concentration of methacrylic acid sulfonate betaine is 47 mg / mL; the molar ratio of methacrylic acid sulfonate betaine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, CuCl2 and CuCl is 1:4:0.4:2; and the temperature of the atom transfer radical polymerization reaction is 25°C and the time is 48 hours.
[0017] The present invention also provides the use of the above-mentioned biological valve material and the above-mentioned multifunctional biological valve material in preparing an artificial biological valve; the artificial biological valve is preferably an artificial heart valve, an artificial pulmonary valve or an artificial venous valve.
[0018] The present invention designs and synthesizes a novel non-glutaraldehyde valve crosslinking agent OX-Br, and then crosslinks porcine pericardium with OX-Br to obtain the heart valve material OX-PP. On the basis of the heart valve material OX-PP, sulfobetaine methacrylate (SBMA) is further introduced through in-situ polymerization to obtain the non-glutaraldehyde crosslinked multifunctional heart valve material SA@OX-PP.
[0019] The heart valve material cross-linked by the non-glutaraldehyde valve cross-linking agent OX-Br of the present invention can be triggered in situ to generate a zwitterionic polymer brush that mimics the cell membrane phospholipid bilayer structure, and exhibits excellent anti-biological contamination ability in anti-protein adhesion experiments, bacterial experiments and a series of in vivo and in vitro blood experiments, excellent biocompatibility and endothelial cell proliferation promotion effects in cell experiments, and low immune rejection reactions and significant anti-calcification performance in animal experiments.
[0020] The novel non-glutaraldehyde valve crosslinking agent of the present invention avoids the problem of residual aldehyde groups in the crosslinking process of the traditional glutaraldehyde crosslinking agent, and can fundamentally avoid the inherent risks of the glutaraldehyde crosslinking agent such as poor biocompatibility and easy calcification.
[0021] The heart valve material of the present invention also has excellent biocompatibility, resistance to protein degradation, resistance to protein adhesion, resistance to bacterial adhesion, anti-coagulation, promotion of endothelialization and anti-calcification properties, and has broad application prospects in the preparation of artificial bio-valves with high comprehensive requirements such as heart valves, pulmonary valves, and venous valves.
[0022] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0023] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 .(A) Schematic diagram of the synthesis process of OX-Br; (B) 1 H NMR spectrum; (C) OX-Br 13 C NMR spectrum, * represents CDCl3.
[0025] Figure 2 .HRMS spectrum of OX-Br.
[0026] Figure 3 .Schematic diagram of SA@OX-PP preparation.
[0027] Figure 4 .(A) Infrared spectra of each sample; (B) Relative weight loss rate after collagenase degradation experiment; (C) Results of anti-protein adhesion experiment; (DF) Adhesion of Escherichia coli and Staphylococcus aureus on the valve surface and adhesion density.
[0028] Figure 5. Anticoagulation experiment. (A) Semi-in vivo blood circulation real picture; (B) Performance of Glut-PP, OX-PP and SA@OX-PP after 1 hour of blood circulation; (C) Performance of Glut-PP, OX-PP and SA@OX-PP after 2 hours of blood circulation; (D) SEM pictures of Glut-PP, OX-PP and SA@OX-PP after the experiment.
[0029] Figure 6 .(A) Extract method-cytotoxicity test results; (B) Endothelial cell adhesion test results, green is live cell staining, red is endothelial cell skeleton and cell nucleus staining; (C) Endothelial cell adhesion density.
[0030] Figure 7 .(A) Immunohistochemistry for CD 3 and CD 68 markers of Glut-PP, OX-PP and SA@OX-PP after implantation; the number of CD 3-positive cells (B) and CD 68-positive cells (C) gathered around the specimen after implantation; (D) Alizarin red-stained sections; (E) Quantitative analysis of calcification of Glut-PP, OX-PP and SA@OX-PP after 30 and 60 days of implantation; *** indicates P < 0.001 compared with Glut-PP; n = 6. DETAILED DESCRIPTION
[0031] Unless otherwise specified, the raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.
[0032] Unless otherwise specified, the temperature of the operating steps in the examples is room temperature (i.e. 25±5°C).
[0033] Unless otherwise specified, the solutions described in the examples are aqueous solutions.
[0034] OX-OH was prepared according to the method described in the literature (T. Yu et al; Nonglutaraldehyde treated porcinepericardium with good biocompatibility, reduced calcification and improved Anti-coagulation for bioprosthetic heart valve applications; Chemical Engineering Journal 414 (2021) 128900).
[0035]
[0036] Example 1: Preparation of non-glutaraldehyde valve crosslinker OX-Br
[0037]
[0038] according to Figure 1 The route shown in A is to synthesize OX-Br. The specific operation is as follows:
[0039] OX-OH (20.00 g, 0.14 mol) and triethylamine (18.14 g, 0.18 mol) were placed in a flask and dissolved with 200 mL of tetrahydrofuran. Then, α-bromoisobutyryl bromide was diluted with 150 mL of tetrahydrofuran and dropped into the flask. After reacting for 24 hours, the mixed solution was centrifuged for 20 minutes, and the supernatant was concentrated with a rotary evaporator. Then, it was recrystallized with ethyl acetate / n-hexane (wherein the volume ratio of ethyl acetate to n-hexane was 1:20) at -20°C to obtain purified OX-Br (29.36 g, yield 72.41%).
[0040] The structures of the obtained OX-Br are respectively 1 H NMR, 13 The results were verified by C NMR and high resolution mass spectrometry (HRMS). Figure 2 and Figure 3 shown.
[0041] Example 2: Preparation of non-glutaraldehyde cross-linked heart valve
[0042] according to Figure 3 The specific steps are as follows:
[0043] Fresh porcine pericardium was collected and washed with deionized water at 4°C and 100rpm shaking for 2 hours; then, the animal biological tissue was decellularized for 3 hours using a mixture of 0.1wt% sodium dodecyl sulfate and 0.1wt% deoxycholic acid to obtain decellularized porcine pericardium (D-PP). The decellularized porcine pericardium was prepared into a size of 110mm×110mm, immersed in a 5% mass concentration OX-Br solution, reacted at 37°C for 5 days, and then taken out and washed with deionized water to obtain the visceral valve: OX-PP.
[0044] OX-PP was immersed in 300 mL of deionized water containing methyl methacrylate sulfobetaine (SBMA, 14.00 g, 0.05 mol), and oxygen was removed by ultrasonic and argon flushing. Then, 1,1,4,7,10,10-hexamethyltriethylenetetramine (HEMETA, 46.00 mg, 0.2 mmol), CuCl2 (2.50 mg, 0.02 mmol) and CuCl (9.90 mg, 0.1 mmol) were transferred to the mixed solution for atom transfer radical polymerization (ATRP) reaction. After reacting at 25 °C for 48 hours, the sample was washed with deionized water and immersed in 5 mg / mL ethylenediaminetetraacetic acid (EDTA) solution overnight to remove unreacted reactants or impurities, taken out, and washed with deionized water to obtain non-glutaraldehyde cross-linked multifunctional heart valve: SA@OX-PP.
[0045] The infrared spectrum of SA@OX-PP is shown in Figure 4 As shown in A, it can be seen that SBMA was grafted successfully.
[0046] The following is the preparation method of the control sample Glut-PP.
[0047] Comparative Example 1: Preparation of Glut-PP
[0048] Prepare a 1.5% glutaraldehyde solution (w / v), add 6% NaCl (w / v) to it, and adjust the pH to 5 with 1M hydrochloric acid. Then place the fixed decellularized porcine pericardium (D-PP) vertically in the glutaraldehyde solution and shake at room temperature for 2 hours to allow the glutaraldehyde solution to penetrate into the porcine pericardium as much as possible. Finally, slowly adjust the pH to neutral with a saturated sodium carbonate solution, shake at room temperature at 120 rpm for 24 hours for cross-linking, take out and ultrasonically clean 5 times to obtain a glutaraldehyde-cross-linked biological heart valve: Glut-PP.
[0049] The beneficial effects of the present invention are demonstrated by experimental examples below.
[0050] Experimental Example 1: Collagenase degradation experiment
[0051] 1. Experimental methods
[0052] After freeze drying, the samples were cut into 1 cm × 1 cm size (n = 5), and their dry weight was weighed and recorded as W1. 1 mg / mL (125 U) collagenase solution was prepared with PBS buffer. Each sample was immersed in 5 mL of collagenase solution and continuously shaken for 24 h (120 rpm) at 37 °C. After the reaction was completed, the samples were centrifuged at 1 × 10 4The sample was centrifuged at rpm for 10 min, then washed three times with PBS buffer, freeze-dried again, and finally weighed for dry weight, which was recorded as W2. The relative weight loss rate of the sample due to enzymatic degradation was calculated by the following formula.
[0053]
[0054] 2. Experimental results
[0055] The experimental results are as follows Figure 4 As shown in Figure B, it can be seen that the non-glutaraldehyde valve crosslinking agent OX-Br of the present invention can successfully crosslink the porcine pericardium, and the obtained non-glutaraldehyde crosslinked heart valves OX-PP and SA@OX-PP can avoid the degradation of collagen, and the effect is equivalent to that of the biological heart valve Glut-PP crosslinked with glutaraldehyde.
[0056] Experimental Example 2: Anti-protein adhesion experiment
[0057] 1. Experimental methods
[0058] Glut-PP, OX-PP, and SA@OX-PP were spread in a 48-well plate and soaked in PBS solution overnight. Then, the samples were incubated with 1 mL FITC-BSA (1 mg / mL) at 37°C. After 2 hours of incubation, the samples were removed from the wells in the dark and rinsed in PBS solution. Finally, the fluorescence intensity of the sample surface was observed using a laser confocal microscope to measure protein adsorption.
[0059] 2. Experimental results
[0060] The experimental results are as follows Figure 4 As shown in C, it can be seen that the non-glutaraldehyde cross-linked multifunctional heart valve SA@OX-PP of the present invention has an excellent anti-protein adhesion effect.
[0061] Experimental Example 3: Anti-bacterial adhesion experiment
[0062] 1. Experimental methods
[0063] Escherichia coli and Staphylococcus aureus were cultured in nutrient solution and diluted to 10% with PBS solution. 7 Plant / cm 2 Glut-PP, OX-PP and SA@OX-PP were then prepared into discs with a diameter of 10 mm and sterilized with ultraviolet light and 75% ethanol. After that, these samples were incubated with diluted solutions containing Escherichia coli or Staphylococcus aureus. After incubation for 6 h, the samples were fixed with 4% paraformaldehyde, gradient dehydrated and dried, and then observed under a scanning electron microscope.
[0064] 2. Experimental results
[0065] The experimental results are as follows Figure 4As shown in DF, it can be seen that compared with the glutaraldehyde cross-linked biological heart valve Glut-PP, the adhesion density of Escherichia coli and Staphylococcus aureus on the SA@OX-PP of the present invention is significantly reduced, indicating that compared with the glutaraldehyde cross-linked biological heart valve Glut-PP, the SA@OX-PP of the present invention has a significantly improved anti-bacterial adhesion effect.
[0066] Experimental Example 4: Anticoagulation Experiment
[0067] 1. Experimental methods
[0068] Samples from different groups were cut into rectangles of 15mm*10mm in size. After the samples were sterilized, they were repeatedly washed with sterile PBS, and all subsequent operations were performed under sterile conditions. The sterilized samples were placed in PVC tubes and assembled into pipelines that could be connected to arteries and veins. The New Zealand white rabbits were then anesthetized with sodium pentobarbital solution, their neck arteries and veins were separated, and they were connected to the pipelines after puncture to establish a circulation loop. After circulating for 1 hour, the pipeline was removed and the samples were washed three times with saline. After the samples were weighed, they were fixed with 2.5% glutaraldehyde solution. After dehydration, critical point drying, gold spraying, and the sample surface was observed with SEM.
[0069] 2. Experimental results
[0070] The experimental results are as follows Figure 5 As shown, it can be seen that compared with the glutaraldehyde-crosslinked biological heart valve Glut-PP, the OX-PP and SA@OX-PP of the present invention have better anti-coagulation ability.
[0071] Experimental Example 5: Test of cell compatibility and ability to promote endothelial cell growth
[0072] 1. Experimental methods
[0073] The cytotoxicity of the samples was evaluated using the extract. Glut-PP, OX-PP, and SA@OX-PP were disinfected by ultraviolet irradiation and 75% ethanol, and then washed 5 times with PBS to remove the residual ethanol solution. The samples (1.0 cm × 3.0 cm) were immersed in 1 ml of complete DMEM medium (containing 10% serum, 1% penicillin mixture) and cultured in a constant temperature incubator at 37 ° C. The extract was prepared after immersion for 72 hours. At the same time, L929 cells were seeded in a 96-well plate at a density of 5000 cells / well. After incubation for 24 hours, the original culture medium was discarded, 150 μL of the extract was added, and incubated for another 24 hours. Finally, each well was washed with 200 μL of PBS solution, 100 mL of CCK-8 solution was added to each well, incubated for 1 hour, and the absorbance value was measured at 450 nm. Promoting endothelial cell growth: Glut-PP, OX-PP, and SA@OX-PP were disinfected by ultraviolet light and 75% ethanol, and then smeared on the bottom of a 48-well plate. Human umbilical vein endothelial cells (HUVECs) were cultured at 2×10 4 The density of cells / well was inoculated in the wells. After incubation for 24h and 48h, the endothelial cells on the sample surface were observed by live cell staining, and layer scanning was performed under a confocal laser microscope. The average density of endothelial cell proliferation and adhesion on the sample surface was obtained by Image-J software. The endothelial cell skeleton on the valve surface was also stained and observed.
[0074] 2. Experimental results
[0075] from Figure 6 A It can be seen that compared with the glutaraldehyde-crosslinked biological heart valve Glut-PP, the OX-PP and SA@OX-PP of the present invention have better cell compatibility.
[0076] from Figure 6 BC shows that compared with the glutaraldehyde-crosslinked biological heart valve Glut-PP, endothelial cells on the OX-PP and SA@OX-PP of the present invention show better proliferation and growth state, and the endothelial cell adhesion density on OX-PP and SA@OX-PP is also significantly improved; in addition, compared with OX-PP, the endothelial cell adhesion density on SA@OX-PP is further improved.
[0077] The above experimental results show that compared with the glutaraldehyde-crosslinked biological heart valve Glut-PP, the OX-PP and SA@OX-PP of the present invention have better cell compatibility and better ability to promote endothelial cell growth.
[0078] Experimental Example 6: Biocompatibility and anti-calcification effect test
[0079] 1. Experimental methods
[0080] The samples were cut into 1cm×1cm size (n=6x 3) and washed three times with PBS. Then they were sterilized by soaking in 75% ethanol solution for 12h. After sterilization, they were washed three times with PBS, rinsing for 15min each time to ensure that the residual ethanol was completely removed. Male SD rats weighing about 50g were selected as implantation objects. The experiment was conducted after one week of feeding. After the rats were anesthetized by intraperitoneal injection of 10% chloral hydrate, two 1cm incisions were made on both sides of the rats' backs and expanded outward to form two pockets that were not connected to each other. The samples were placed in the two pockets, and the membranes were kept flat during implantation. After implantation, the wounds were sutured with sutures and wiped with iodine to prevent bacterial infection. The materials were taken out at 30 days and 60 days respectively. The taken materials were divided into two parts. One part was fixed with tissue fixative and embedded in paraffin for immunohistochemistry and staining. The other part of the materials was directly used for quantitative analysis of calcification.
[0081] 2. Experimental results
[0082] from Figure 7 AC It can be seen that compared with the glutaraldehyde-crosslinked biological heart valve Glut-PP, the OX-PP and SA@OX-PP of the present invention have significantly improved biocompatibility.
[0083] from Figure 7 It can be seen from DE that compared with the glutaraldehyde-crosslinked biological heart valve Glut-PP, the OX-PP and SA@OX-PP of the present invention have significantly improved anti-calcification effects.
Claims
1. A valve cross-linking agent, characterized in that: Its structure is as follows:
2. A biological valve material, characterized in that: The invention is a product prepared by taking pericardium and the valve cross-linking agent described in claim 1 as raw materials.
3. The bioprosthetic valve material according to claim 2, characterized in that: The pericardium is pericardium after decellularization.
4. The bioprosthetic valve material according to claim 3, characterized in that: The decellularized pericardium is decellularized porcine pericardium.
5. A method for preparing the biological valve material according to any one of claims 2 to 4, characterized in that: It includes the following steps: The pericardium is immersed in a valve cross-linking agent solution and reacted at 35-40° C. for 3-7 days to obtain a biological valve material; the mass concentration of the valve cross-linking agent solution is 3%-7%.
6. The method according to claim 5, characterized in that: The reaction temperature is 37° C., the reaction time is 5 days, and the mass concentration of the valve cross-linking agent solution is 5%.
7. A multifunctional bioprosthetic valve material, characterized in that: The invention is a product obtained by atom transfer free radical polymerization reaction between the biological valve material described in any one of claims 2 to 4 and methacrylic acid sulfobetaine.
8. A method for preparing the multifunctional bioprosthetic valve material according to claim 7, characterized in that: The method comprises the following steps: immersing the biological valve material according to any one of claims 2 to 4 in a solution containing methacrylic acid sulfonate betaine, removing oxygen, adding a ligand and a catalyst, performing atom transfer free radical polymerization, purifying, and obtaining a multifunctional biological valve material.
9. The method according to claim 8, characterized in that: In the solution containing methacrylic acid sulfonate betaine, the concentration of methacrylic acid sulfonate betaine is 45-50 mg / mL; the ligand is 1,1,4,7,10,10-hexamethyltriethylenetetramine, the catalyst is CuCl2 and CuCl, and the molar ratio of methacrylic acid sulfonate betaine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, CuCl2 and CuCl is 1:(2-8):(0.2-0.8):(1-4); the temperature of the atom transfer radical polymerization reaction is 20-30°C and the time is 24-72 hours; the purification method is to soak in an ethylenediaminetetraacetic acid solution and then wash with water.
10. The method according to claim 9, characterized in that: In the solution containing methacrylic acid sulfonate betaine, the concentration of methacrylic acid sulfonate betaine is 47 mg / mL; the molar ratio of methacrylic acid sulfonate betaine, 1,1,4,7,10,10-hexamethyltriethylenetetramine, CuCl2 and CuCl is 1:4:0.4:2; the temperature of the atom transfer radical polymerization reaction is 25°C and the reaction time is 48 hours.
11. Use of the biological valve material according to any one of claims 2 to 4 or the multifunctional biological valve material according to claim 7 in the preparation of artificial biological valves.
12. The use according to claim 11, characterized in that: The artificial bio-valve is an artificial heart valve, an artificial pulmonary valve or an artificial venous valve.
